2010
DOI: 10.1080/10826068.2010.488987
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yeast, Fermentation Time, and Preservation Methods on Tarhana

Abstract: The physicochemical properties of tarhana soup produced with different dough treatments, fermentation times, and preservation methods were examined. Tarhana doughs were prepared with yogurt (control) or baker's yeast (Saccharomyces cerevisiae) and fermented for 3 days. Samples were taken at 24, 48, and 72 hr. Samples were then preserved via one of four methods: sun dried, dried in the shade, vacumn dried, and frozen. Frozen samples produced lower organic acid levels after 72 hr of fermentation in both control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
7
7
1
Order By: Relevance
“…Higher lactic acid content recorded for the sourdough fermented with L. brevis, L. plantarum, and L. sanfranciscencis starter culture could be ascribed to improved activities of LAB, which resulted in the rapid production of lactic acid in the sourdoughs. This result was in agreement with the findings of Gurbuz et al (2010), who reported that LAB grows and produce lactic acid more slowly in mixtures containing yeasts than in pure culture. Sourdough with high acid will have improved proteolysis and protein solubility.…”
Section: Organic Acids Ethanol and Sugar Contents Of The Rice Bran Ssupporting
confidence: 83%
See 3 more Smart Citations
“…Higher lactic acid content recorded for the sourdough fermented with L. brevis, L. plantarum, and L. sanfranciscencis starter culture could be ascribed to improved activities of LAB, which resulted in the rapid production of lactic acid in the sourdoughs. This result was in agreement with the findings of Gurbuz et al (2010), who reported that LAB grows and produce lactic acid more slowly in mixtures containing yeasts than in pure culture. Sourdough with high acid will have improved proteolysis and protein solubility.…”
Section: Organic Acids Ethanol and Sugar Contents Of The Rice Bran Ssupporting
confidence: 83%
“…Rice bran sourdough fermented with yeast (control sample) had the highest glucose (1.1 g/100g) and maltose content (1.06 g/100g) compared to the sourdoughs fermented with mixed culture or L. brevis, L. plantarum, and L. sanfranciscencis. This could be because yeasts and LAB have different kinetics for soluble carbohydrate uptake (Gurbuz et al, 2010). This observation was in agreement with the report of Colla et al (1996).…”
Section: Organic Acids Ethanol and Sugar Contents Of The Rice Bran Ssupporting
confidence: 83%
See 2 more Smart Citations
“…It was proven that this species stimulates the fermentation of tarana by affecting lactic acid bacteria and yeast Saccharomyces cerevisiae. In traditional medicine, it is used as a fungicide for the treatment of wounds and stomach ulcers, also, as digestive and anti-spasm agent (Baser et al, 1998;Cakilcioglu and Turkoglu, 2010;Degirmencioglu et al, 2005;Gurbuz et al, 2010;Ozdemir et al, 2007). In addition, the seeds and the roots of this taxon have been effectively applied in the treatment of epilepsy (Eadie, 2004).…”
Section: Introductionmentioning
confidence: 99%